A Feasibility Study of the Salted Fish Processing Business in Sei Sembilang Hamlet, Sungsang IV Village, Banyuasin Regency, South Sumatra - Desliana Opie Harliani Opie; Tiara Santeri; Rr Dyah Paramitha Mentari; Ragil Susilowati; Pipi Anggraini; Teni Agustin (Journal of Global Sustainable Agriculture, 2025)
Dusun Sei Sembilang in Sungsang IV Village is one of the coastal areas in Banyuasin Regency that has significant potential in fishery product processing, particularly salted fish. This study analyzes the feasibility of salted fish businesses in Dusun Sei Sembilang, Sungsang IV Village, Banyuasin Regency. The research employed a descriptive quantitative approach, with data collected through direct observation of production activities, questionnaires administered to 10 salted fish producers, and in-depth interviews with group leaders and community representatives. Data were analyzed from technical, market, managerial, and financial perspectives. Statistical analyses included cost–revenue analysis and financial feasibility assessment using NPV, IRR, B/C Ratio, and Payback Period, supported by descriptive statistical evaluation. The results show that raw materials are available throughout the year, the production process is simple, and the selling price remains stable at Rp 80,000 per kilogram. The business group operates through a collaborative work system, although financial recording is still limited. Financial analysis indicates that the business is highly feasible, with a positive NPV of Rp 5,714,500, an IRR of 265%, a B/C Ratio of 6.71, and a Payback Period of 0.37 years. Therefore, salted fish enterprises in this area are considered feasible to develop and have the potential to increase the income of coastal communities.